Designing Rawa Pening as a new nature-based tourism area - Ashri Prawesti D; Widia Nur Intan Paramita; I Putu Krisna Arta Widana; Ni Luh Ayu Kartika Yuniastari Sarja (International Journal of Green Tourism Research and Applications, 2022)
The purpose of this research is to determine the potential of Rawa Pening area which can be developed as a new nature-based tourism area in Central Java, Indonesia. The research method is qualitative research. This method of data collection during the Covid 19 pandemic used more secondary data than primary data. The interview method with resource persons through field survey method is carried out to complete the analysis of this research. The findings resulting from this research are on several potentials that can be developed, both physical and non-physical potentials. The results of this research are ideas and suggestions through the plan of design ideas or initial concepts in developing new nature-based tourist areas.